Development of a web-based tool for undergraduate engagement in medical research; the ProjectPal experience - Rawson,T; Sivakumaran,P; Lobo,R; Mahir,G; Rossiter,A; Levy,J; McGregor,A; Lupton,M; Easton,G; Gill,D (BMC Medical Education, 2018)
BackgroundWe report the development and evaluation of a web-based tool designed to facilitate student extra-curricular engagement in medical research through project matching students with academic supervisors.UK based university students were surveyed to explore their perceptions of undergraduate research, barriers and facilitators to current engagement. Following this, an online web-based intervention (www.ProjectPal.org) was developed to support access of students to research projects and supervisors. A pilot intervention was undertaken across a London-based university in January 2013 to February 2016. In March 2016, anonymised data were extracted from the prospective data log for analysis of website engagement and usage. Supervisors were surveyed to evaluate the website and student outputs.ResultsFifty-one students responded to the electronic survey. Twenty-four (47%) reported frustration at a perceived lack of opportunities to carry out extra-curricular academic projects. Major barriers to engaging in undergraduate research reported were difficulties in identifying suitable supervisors (33/51; 65%) and time pressures (36/51; 71%) associated with this. Students reported being opportunistic in their engagement with undergraduate research. Following implementation of the website, 438 students signed up to ProjectPal and the website was accessed 1357 times. Access increased on a yearly basis. Overall, 70 projects were advertised by 35 supervisors. There were 86 applications made by students for these projects. By February 2016, the 70 projects had generated 5 peer-review publications with a further 7 manuscripts under peer-review, 14 national presentations, and 1 national prize.ConclusionThe use of an online platform to promote undergraduate engagement with extra-curricular research appears to facilitate extra-curricular engagement with research. Further work to understand the impact compared to normal opportunistic practices in enhancing student engagement is now